Evaluasi Penerapan Pajak Penghasilan Atas Kebijakan PP 46 Tahun 2013 Dan PP 23 Tahun 2018 pada CV Rizqi Utama sebagai Pelaku Usaha Mikro Kecil Menengah - Siti Muthia Purnamasari; Yeti Apriliawati (Indonesian Accounting Literacy Journal, 2021)
Tax is one form the state revenue which is the main source of government administration, development, and to improve people's welfare. Usaha Mikro Kecil Menengah (UMKM) are one of the most sought after business activities and have an important role in driving Indonesia's growth. From the results of the assessment of UMKM on Indonesian finances, it is hoped that this will have a positive impact on the taxation sector. Government efforts to maximize tax revenue for UMKM are issued with PP 23 of 2018 as change of former PP 46 of 2013. CV Rizqi Utama is a business entity engaged in the trade of goods and printing services in accordance with their tax requirements based on PP 23 of 2018 as change of former PP 46 of 2013. The research method used is qualitative-quantitative with the type of descriptive research with research methods and case study research. Data retrieval is done by observation, interview, documentation, and combination / triangulation. The results of the study explained that the fulfillment of tax obligations carried out by CV Rizqi Utama had not been carried out in accordance with applicable regulations and for this matter CV Rizqi Utama could be subject to administrative sanctions in the form of interest and/or penalties.